IMPLEMENTASI METODE KLASIFIKASI NAIVE BAYES UNTUK MEMPREDIKSI KUALITAS CABAI - Abd. Ghofur (Department of Science and Technology Ibrahimy University, 2016)
Image processing can proces many colors in the fruit, especially in fruit of chili. There are several colors contained in the chili fruit that is green, orange and red. Chilies are not predictable price because the chili have fluctuate prices, the chili can be determined is only the quality. The main parameters of this research are chili size and color of the chili, because these fitures can be processed to get output, namely the prediction of the chili quality. Some processes be used to predict the chili. These processes are extraction of color RGB, LAB conversion of to RGB and Grayscale, level adjustment, color Region. Some of these processes do to get a percentage of the stalk (after being separated by body of the chili) and percentage of the maturity. The last proces is classifying the chili that have been obtained percentage of stalk and maturity then using Naive Buyes Classifier metod for classifying to four kind fo quality, namely quality A, B, C and D. These qualities classification are A : consists of red chilies or ripe chili that has big size, B : consists of measuring big green chili, C : consists of small pieces of red chili and D : comprises small green chili.